Prolidase deficiency presenting as inflammatory bowel disease in an infant - Srinivasan, Prerana Vaishnavi; Srinivasan, Ramesh (International Journal of Contemporary Pediatrics, 2026)
Lupi A, Tenni R, Rossi A, Cetta G, Forlino A. Prolidase deficiency: biochemical and clinical heterogeneity. Orphanet J Rare Dis. 2008;3:22. Forlino A, Marini JC. Prolidase deficiency. GeneReviews®. Seattle (WA): University of Washington. 2017. Available at: https://www.ncbi.nlm.nih.gov/books/NBK1546/. Accessed on 06 December 2025. Roy A, Raymond K, Koudelka CW, Wang J, Perry J, Reardon G, et al. Prolidase deficiency presenting with inflammatory bowel disease-like colitis. J Pediatr Gastroenterol Nutr. 2014;58(3):e25-8. Di Rocco M, Gatti R, Gandullia P, D’Alessandro M, Parini R, Dionisi‑Vici C. Gastrointestinal involvement in prolidase deficiency. J Inherit Metab Dis. 2007;30(3):399-404. Rossignol F, Duarte Moreno MS, Benoist JF, Boehm M, Bourrat E, Cano A, et al. Quantitative analysis of the natural history of prolidase deficiency—description and systematic review. Genet Med. 2021;23(9):1604-15. Kuloglu Z, Kansu A, Serwas N, Demir AM, Yaman A, Ensari A, et al. Inflammatory bowel disease-like phenotype in a young girl with prolidase deficiency. Genet Couns. 2015;26(2):205-11. Rizvi SA, Elder M, Beasley G. A novel manifestation of prolidase deficiency in a toddler diagnosed with very-early-onset Crohn’s disease. J Pediatr Gastroenterol Nutr. 2019;69(3):e89-90. Madhusudan M, Sankaranarayanan S, Ramamoorthy R, Munirathnam D, Sivasankaran M. Prolidase deficiency in very early onset inflammatory bowel disease. Indian J Pediatr. 2021;88(5):503. Aijaz A, Parrey A, Ismail M, Sadaqat M, Noor M, Amin Y, et al. A case of prolidase deficiency presenting as upper gastrointestinal bleed. Ann Clin Case Rep. 2022;7:2089. Gopalakrishna H, Asif B, Rai A, Conjeevaram HS, Mironova M, Kleiner DE, et al. Chronic liver disease in patients with prolidase deficiency: a case series. Case Rep Gastroenterol. 2024;18(1):49-57. Castro M, Martinez C, Brathwaite C, Bromberg R, Rodriguez AM, Hernandez E. Porto-sinusoidal vascular disorder in a pediatric patient with prolidase deficiency: a case report. JPGN Rep. 2025;6(4):519-23.